Challenges reflected on by student teachers of English during teaching practice - Molotja, T.W.; Maruma, M. (South African Journal of Higher Education, 2018)
Teachers are faced with enormous emotional and physical demands on a daily basis; and have little or no time to reflect on their practice. This becomes problematic for student-educators when they are supposed to go through their practice. The dual purpose of this study was, firstly to investigate English language student-educators’ challenges experienced during their teaching practice sessions; and secondly: to recommend better strategies through which such challenges could be addressed. The study was informed by Vygotsky (1978)’ Social Constructivist theory, which emphasises social learning and interactive teaching. Based on an action research interpretivist’s paradigm, using a qualitative approach, 14 semi-structured group interviews were conducted with 100 student-educators purposefully sampled for this study. The participants wrote a once-off reflective essay as part of their practice teaching portfolio. A document analysis approach was applied while reading the essays to identify the teaching challenges. Among others: lesson planning, alignment of teacher’s and learners’ activities and meaningful content presentations were confirmed to be the most problematic. These findings show a critical need to design strategies to encourage reflective practice in the undergraduate teacher programme. Key words: student-educators, reflective practice, teaching challenges, teaching practice